Comparative Studies of National Business Cultures in the Countries of Central and Eastern Europe: the Basics for Improving International Entrepreneurship in Poland and Ukraine - Beata Glinkowska-Krauze; Iegor Chebotarov; Viacheslav Chebotarov (Comparative Economic Research. Central and Eastern Europe, 2020)
Based on the work of Hofstede, Trompenaars, Lewis, and Rapaille, the founders of the theory of national business cultures and comparative economic studies, the characteristics of corresponding scientific areas are identified: cross-cultural management, cross-cultural communications, and cross-cultural marketing, including their methodological and practical aspects. Using the classic measuring parameters of national business cultures ("Individualism," "Power Distance," "Masculinity," "Uncertainty Avoidance," "Long-Term Orientation," "Indulgence"), a comparative analysis is carried out on the example of Poland, Ukraine, Germany, France, and Hungary; the results of the authors' own development of this interdisciplinary problem are presented. On this basis, new approaches are proposed in establishing mutually beneficial international cooperation between Polish and Ukrainian enterprises, not only in Europe but also in other regions of the world.
Keywords: O57; F23; 330; comparative studies; national business culture; measuring parameters of national business cultures; management; communications; marketing; internationalization; Poland; Ukraine